Bioremediation of poultry feather waste- a review - D. Thyagarajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Poultry farming is growing at 8% Compound Annual Growth Rate (CAGR) in layer and 12% CAGR in broiler farming. Consequent to the growth of the poultry farming activity, eco-friendly approach to utilize the waste into value added products are of current importance. Waste on one hand is responsible for adding pollutants to the environment; on the other hand it causes major problems in handling. In domesticated birds, feather waste accounts to 7% of the body weight of the birds. At present it is being disposed off without any solid waste treatment. Feather is having advantage of containing valuable sulphur containing amino acids like cysteine and methionine. Over the years, feather meals are produced using thermal and chemical processes. However these methods are having disadvantages of energy expensive and poor end products. Now lot of research work are attempted through bioremediation of the feather meal. Even though much of the investigations are on the laboratory side, applications of this technology are yet to be taken up, either due to lack of detailed knowledge on these technologies or lack of information about various bacteria and fungi available for this purpose. In this paper various bacteria like Bacillus subtilis, Bacillus pumilis, Bacillus altitudinis, Bacillus licheniformis, Pseudomonas microphilus, Leuconostoc, Thermus aquaticus and Fervidobacterium pennavorans for their potential as keratinolytic activity are discussed. Similarly role of certain fungi like Aspergillus niger, Penicillium citrinum, Trichoderma viride, Alternaria tenuissima, Chrysosporium tropicum and Fusarium culmorum in bioremediation of the feather to feather meal are also elaborated. Altogether bioremediation of feather meal concurrently adhere to integrated eco-friendly waste disposal with due importance to maintaining biodiversity of the living organism in the ecosystem.